Education about the Impact of Early Marriage on Teenagers: Edukasi tentang Dampak Pernikahan Dini pada Remaja - Pratiwi, Sulfa Indah; Nurfatimah, Nurfatimah; Longgupa, Lisda Widianti; Lewa, Abd. Farid; Yuda, Silfana (Jurnal Pengabdian Bidan Nasuha, 2023)
Introduction: Early marriage is not a new phenomenon, both in Indonesia and other countries. The Central Statistics Agency records that the prevalence of early marriage is more common in rural areas, reaching 27.11%. In Parigi Moutong District, the rate of early marriage has been increasing year by year. Purpose: The purpose of this activity is to educate teenagers about the dangers of early marriage, with the aim of producing quality families and ultimately generating a quality generation for Indonesia. Methods: This activity will be conducted in Siniu Village. The target audience for this activity is teenagers residing in Siniu Village. The method of this activity involves conducting a pre-test questionnaire, followed by providing counseling using leaflets as a medium, and concluding with a post-test questionnaire. Results: The evaluation results from the questionnaire indicate an increase in teenagers' knowledge from 60% to 90% regarding the dangers of early marriage. Conclusion: It is expected that teenagers will take the initiative to learn about the subject of early marriage without any external pressure, thus realizing the importance of this information for themselves and others.